Implementasi Nilai Religiusitas Melalui Program Ekstrakurikuler di MAN 2 Langkat - Fiola Vitaloca; Nurmisda Ramayani (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Extracurricular programs are educational programs carried out outside standard curriculum lesson hours. The aim is to develop students' religious values ​​so that they become better individuals and to help parents and educators in providing religious-based teaching through extracurricular programs created by the school/madrasah. The type of research carried out in this research is qualitative. Meanwhile, information collection is carried out through observation, interviews and documentation. The research subjects in this thesis are the school principal, extracurricular supervisors, and students. The results of this research show that: first, the value of religiosity at MAN 2 Langkat varies greatly, both in terms of habituation within the standard curriculum such as daily learning, and outside the standard curriculum such as extracurricular activities. This value of religiosity has indeed been implemented from the inception of the institution until now. With the aim of developing the value of religiosity in students in everyday life. Second, the extracurricular programs at MAN 2 Langkat are all running effectively, including extracurricular programs in the fields of religion, arts, school security, environment, health and sports. Third, implementing the value of religiosity through extracurricular programs at MAN 2 Langkat is very diverse. In religious programs, students can develop their Al-Quran reading skills, memorization skills, and lecture skills because of the existence of religious extracurricular programs such as KKD and LPTQ. In general extracurricular programs such as PMR, UKS, SISPALA, OSIS, LPM, PKS, ACHERY, PRAMUKA, KIR, CLUB OLYMPIADE, PASKIBRA, PIK-R and FUTSAL, the value of religiosity is also applied, such as how to dress, politeness when speaking, and maintaining environmental cleanliness, and please help.